2010
DOI: 10.1093/europace/euq431
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity associated with three different antiplatelet regimens in patients undergoing implantation of cardiac rhythm management devices

Abstract: Dual AP therapy and OAC + AP therapy is strongly associated with a significant risk of pocket haematoma, longer hospital stays, and unscheduled follow-up visits. Importantly, surgical revision of the pocket was associated with enoxaparin 'bridging' strategy but was never necessary in patients taking exclusively antiaggregant agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…This is a retrospective single-center cohort study of 1,091 patients in whom devices were implanted over 1 st October 2011 to 31 st December 2014. Patients were consecutively included, totaling 1,316 altogether, but were excluded if they had missing demographic data such as unrecorded international normalized ratio (INR). Some operators also only had one or two cases, and these were excluded to prevent an additional source of bias.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a retrospective single-center cohort study of 1,091 patients in whom devices were implanted over 1 st October 2011 to 31 st December 2014. Patients were consecutively included, totaling 1,316 altogether, but were excluded if they had missing demographic data such as unrecorded international normalized ratio (INR). Some operators also only had one or two cases, and these were excluded to prevent an additional source of bias.…”
Section: Methodsmentioning
confidence: 99%
“…Hematomas are painful and may necessitate changes to anticoagulation regimes in patients at risk of thromboembolic events . They may also require reoperation for drainage or prolonged hospital admissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient related risks for complications have included clopidogrel or heparin anticoagulant administration (but not warfarin or aspirin),25 dual antiplatelet therapy or low molecular weight bridging therapy,26 chronic renal disease, dementia, and chronic lung disease 19. Women have been observed to have a 1.5- to 1.7-fold higher risk of a major adverse event using multivariate analysis.…”
Section: Acute Complicationsmentioning
confidence: 99%
“…Another recent prospective observational study 11 found that dual antiplatelet therapy in patients undergoing implantation of cardiac rhythm management devices is associated with an increased risk of pocket hematoma, longer hospital stays, and unscheduled follow‐up visits.…”
Section: Discussionmentioning
confidence: 99%